PERAN PEMANGKU KEPENTINGAN DALAM MEMBANGUN ALAT SERTIFIKASI PENGELOLAAN HUTAN PRODUKSI LESTARI (S-PHPL) YANG KREDIBEL, EFISIEN, DAN ADIL - Fachrulyan Marhandhika Heruono; Firman Rosjadi Djoemadi; Sugeng Hariadi (Perpustakaan Universitas Surabaya, 2018)
Certification of sustainable production forest management (PHPL certication) is a tool in timber legality verification system (SVLK) established and must be applied by holders of forest product utilization permit. PHPL certication is a forest certification scheme to ensure that forest management has managed sustainable production forests. The PHPL certication system is considered to encourage better forest management and preserve the existing resources, so that Indonesian timber export products can be declared legal because they come from certified sources. This research is qualitative-intrerpretative. The variables used in this study are credible, efficient, and fair.